Potential Using of Mixed Microalgae in the Bioremediation of Domestic Effluents - Ajaweed, Aseel Najeeb (Iraqi Journal of Science, 2022)
Microalgae widely used for bioremediation of inorganic (NH4and PO4) nutrients as single isolates. This study aims to use a mix microalgae isolated from Dijlah river for bioremediation of municipal waste water .The experiments had been start with two different concentrations of nutrients. NH4-N values were 23.4 and 31.7mg/l, phosphorus PO4-P 6.7and 10.7 mg/ l and BOD5 were 66 and 83 mg/l. both cycles of treatment showed complete removal for NH 4-N and PO4-P levels after treatment were 1.7 and 0.7 mg/l for both of treatment cycle .Biological oxygen demand reduced to lowest value were18.9 in 2nd cycle while in 1st cycle of treatment reduced to21.3mg/l.The results showed that mix microalgae have the ability to remove nutrients and organic pollutants at different levels even at pH variation during experiment.